2015
DOI: 10.1159/000373991
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Suppressing Effect of MiR-4458 on Human Hepatocellular Carcinoma

Abstract: Background: Besides multiple genetic and epigenetic changes of protein coding genes in hepatocellular carcinoma (HCC), growing evidence indicate that deregulation of miRNAs contribute to HCC development by influencing cell growth, apoptosis, migration, or invasion. IKBKE is amplified and over-expressed in a large percentage of human breast tumors and identified as an oncogene of human breast tumor. Microarray analysis showed that miR-4458 was down-regulated in HCC tissues. Methods: The level of miR-4458 was up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Recently, two studies indicated that miR-4458 is a tumor suppressor that is down-regulated in human hepatocellular carcinoma and colon cancer and might influence cell viability in these two cancer types [12,13] . Moreover, miR-4458 was shown to be a potential prognosis predictor for hepatocellular carcinoma patients [12] and inhibited glycolysis and lactate production in colon cancer cells [13] . Mechanistically, direct interaction between miR-4458 and the 3'UTR of IKBKE or HK2 mRNA was identified in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, two studies indicated that miR-4458 is a tumor suppressor that is down-regulated in human hepatocellular carcinoma and colon cancer and might influence cell viability in these two cancer types [12,13] . Moreover, miR-4458 was shown to be a potential prognosis predictor for hepatocellular carcinoma patients [12] and inhibited glycolysis and lactate production in colon cancer cells [13] . Mechanistically, direct interaction between miR-4458 and the 3'UTR of IKBKE or HK2 mRNA was identified in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that miR-4458 expression is dysregulated in hepatocellular carcinoma [12] and colon cancer [13] . Those studies reported that miR-4458 is a tumor suppressor that is down-regulated in hepatocellular carcinoma and colon cancer, and that the high expression of miR-4458 suppresses the proliferation of tumor cells [12,13] . However, the role of miR-4458 in NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is one of the predominant causes of cancer-associated mortality worldwide (8). HCC cell metastasis is the primary cause of HCC development.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the continuous increases in 5-year survival for HCC due to advances in combined therapy with surgery, radiotherapy and chemotherapy, some patients still suffer from poor outcome due to malignant growth and metastases of HCC [1][2][3][4]. Thus, a further understanding of the molecular mechanisms underlying the progression and metastases of HCC would improve the current therapy [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%